A preparation method of a mechanical gradient electrode applied to a flexible battery

CN116470012BActive Publication Date: 2026-10-13GUIZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310203070.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-06
Publication Date
2026-10-13
Estimated Expiration
2043-03-06

AI Technical Summary

Technical Problem

虽然这些做法能实现在弯曲等条件下稳定的电源供应,但一些在阳极或者阴极中的柔性物质会由于高氧化或还原环境而发生降解,并且,想要制备具有极低弯曲半径(500-1000μm)尺度的柔性电极通过上述方法难以实现

Benefits of technology

[0026]1、本发明在整个制备过程所用原料与传统的锂离子电池电极的一致,在原料上不需要其他的投入,相较于其他柔性电极具有成本低、工艺简单、绿色环保等优点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116470012B_ABST
    Figure CN116470012B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a mechanical gradient electrode applied to a flexible battery. Firstly, a plurality of mixtures of active substances, graphene and carbon black conductive agents are prepared; then, appropriate PVDF solutions are added to prepare active substance and graphene slurries containing different concentrations of PVDF; finally, the above slurries are sequentially coated on a current collector by a multiple-coating-drying method according to the concentration from small to large to prepare the mechanical gradient electrode. The mechanical gradient electrode group prepared by the application has the advantages of bend resistance, twist resistance, high energy density, good stability, long service life and the like when applied to the flexible battery. Moreover, the application has simple process, same raw materials as a traditional preparation scheme, small equipment investment and easiness in industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of flexible battery technology, and more specifically, to a method for preparing a mechanical gradient electrode for use in flexible batteries. Background Technology

[0002] Flexible batteries are a type of energy storage device that, compared to traditional batteries, possess characteristics such as bendability, folding, compression, and torsion, making them highly promising for applications in wearable devices, electronic medical devices, and other fields. Their development history spans over a century. Initial research on flexible batteries was based on alkaline and all-polymer batteries. Later, due to the advantages of lithium-ion batteries, such as high energy density, long lifespan, low self-discharge rate, fast charging, and no memory effect, research on flexible batteries shifted to lithium-ion batteries.

[0003] Flexible lithium-ion batteries are developed from traditional lithium-ion batteries, with the electrode being the most crucial component. To achieve flexibility in the electrode, researchers typically approach the issue from both intrinsic and composite perspectives, developing flexible electrodes or coating traditional electrode materials onto flexible substrates. Examples include fabricating electrodes by mixing graphene oxide and silicon nanoparticles and then filtering the mixture to form a film, or embedding active materials into a polymer substrate. While these methods can achieve stable power supply under bending conditions, some flexible materials in the anode or cathode can degrade due to high oxidation or reduction environments. Furthermore, achieving flexible electrodes with extremely low bending radii (500-1000 μm) using these methods is difficult. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing a mechanical gradient electrode for flexible batteries. This method has the advantages of simple raw materials, simple and efficient preparation method, low production cost and low equipment investment. Moreover, the mechanical gradient electrode prepared by this method has good flexibility while ensuring high volumetric energy density.

[0005] The above-mentioned technical objective of the present invention is achieved through the following technical solution: a method for preparing a mechanical gradient electrode for flexible batteries, comprising the following steps:

[0006] S1. The active material, graphene and carbon black conductive agent are thoroughly mixed to obtain two mixtures, and each mixture is divided into four equal parts;

[0007] S2. Dissolve polyvinylidene fluoride (PVDF) powder in N-methylpyrrolidone (NMP) solution to prepare PVDF solution;

[0008] S3. Add the PVDF solution prepared in S2 to the four active material mixtures prepared in S1 to obtain four active material slurries with different PVDF contents;

[0009] Add the PVDF solution prepared in S2 to the four graphene mixtures prepared in S1 to obtain four graphene slurries with different PVDF contents.

[0010] Each portion of slurry is thoroughly mixed using a stirring degassing machine, and then NMP is added to each portion of slurry to ensure that the viscosity of each portion of slurry is consistent.

[0011] S4. Use a scraper to scrape the active material slurry with the lowest PVDF content onto the current collector. After the coating is completed, place it in an oven to dry, and obtain a single-layer electrode.

[0012] The graphene slurry with the lowest PVDF content was scraped onto the current collector using a scraper. After the coating was completed, it was placed in an oven to dry, thus obtaining a single-layer electrode.

[0013] S5. Use different scrapers with larger coating gaps to repeat the operation in S4 with the remaining three portions of active material slurry in order of PVDF content from small to large, and finally obtain mechanical gradient electrode one;

[0014] By successively using a scraper with a larger coating gap, the remaining three portions of graphene slurry are processed in order of increasing PVDF content, repeating the operation in step S4 to finally obtain the mechanical gradient electrode two.

[0015] The present invention is further configured such that the active material is used to prepare the positive electrode, and graphene is used to prepare the negative electrode. Graphene is used as the negative electrode material of the battery because it possesses high stability, high conductivity, high specific surface area, and high flexibility.

[0016] The present invention is further configured such that the mass ratio of the active material to the carbon black conductive agent in S1 is 96:4, and the mass ratio of graphene to the carbon black conductive agent is 96:4. Adding the carbon black conductive agent improves conductivity, mechanical properties, and stability.

[0017] The present invention is further configured such that the active material in S1 is NCM111. NCM111 is an active material with high energy density, high cycle stability, low self-discharge rate, and relatively low cost.

[0018] The present invention is further configured such that the mass concentration of PVDF in S2 is 5%. A higher concentration results in a higher viscosity of the system, which is not conducive to subsequent operations; a lower concentration results in a lower viscosity, which is also not conducive to subsequent coating operations and leads to the waste of NMP.

[0019] The present invention is further configured such that: the PVDF content in the active material slurry in S3 is 2%, 3.5%, 5%, and 6.5%, respectively; and the PVDF content in the graphene slurry is 2.5%, 4.5%, 5%, and 7%. Excessive PVDF content will reduce the specific surface area and porosity of the electrode, decrease the contact area between the electrode and the electrolyte, and reduce charge transport efficiency, thereby affecting the battery's discharge performance and cycle life. Insufficient PVDF content will decrease the electrode's flexibility and other mechanical properties.

[0020] The present invention is further configured to: control the slurry in S3 to circulate three times in the stirring degassing machine for a total of 90 minutes.

[0021] The present invention is further configured such that: the current collector for coating the active material slurry in S4 is an aluminum foil, and the current collector for coating the graphene slurry is a copper foil.

[0022] The present invention is further configured such that: in S4, the coating gap of the doctor blade for applying the active material slurry is 50 μm, and the coating gap of the doctor blade for applying the graphene slurry is 75 μm.

[0023] The present invention is further configured such that the temperature of the oven in S4 is 50°C.

[0024] The present invention is further configured such that: in step S5, the coating gaps of the scraper used for scraping the active material slurry are 75, 100 and 150 μm, respectively, and the coating gaps of the scraper used for scraping the graphene slurry are 100, 150 and 200 μm, respectively.

[0025] In summary, the present invention has the following beneficial effects:

[0026] 1. The raw materials used in the entire preparation process of this invention are the same as those used in traditional lithium-ion battery electrodes. No other input is required in terms of raw materials. Compared with other flexible electrodes, it has the advantages of low cost, simple process, and green environmental protection.

[0027] 2. The preparation process of the present invention is simple, does not require special equipment, and can realize large-scale production and industrial transformation based on traditional electrodes.

[0028] 3. The electrode prepared by this invention has high energy density, long service life, and excellent bending resistance. Attached Figure Description

[0029] Figure 1 A schematic diagram illustrating the method for quantifying the bending radius during electrode bending performance testing;

[0030] Figure 2 For testing the bending performance of the electrodes;

[0031] Figure 3 Electrochemical performance testing of electrodes based on coin cells;

[0032] Figure 4 Stability testing of electrodes based on coin cells;

[0033] Figure 5 Electrochemical performance testing and stable power supply status of the electrode based on a pouch cell;

[0034] Figure 6 The charge-discharge curves are for the folded pouch cell. Detailed Implementation

[0035] The following is in conjunction with the appendix Figure 1-6 The present invention will be described in further detail below.

[0036] Example: A method for preparing a mechanical gradient electrode for flexible batteries, using NMP as a solvent to prepare a 5% (w / w) PVDF solution. NCM111 and graphene are mixed with carbon black conductive agent at a mass ratio of 96:4 to obtain mixtures, which are then divided into four equal parts. Calculations are performed to add appropriate volumes of PVDF solvent to the mixtures, ensuring that the PVDF mass fraction (excluding NMP) in the NCM111 mixture is 2%, 3.5%, 5%, and 6.5%, respectively, and the PVDF mass fraction (excluding NMP) in the graphene mixture is 2.5%, 4.5%, 5%, and 7%, respectively. The mixture is then subjected to planetary centrifugation for three cycles (totaling 90 minutes) to obtain slurries. An appropriate amount of NMP solution is added to the slurries to ensure that the viscosity of all slurries remains consistent. Using aluminum foil as a substrate, NCM111 slurry was coated and dried four times in order of increasing PVDF content (50℃). The coating gaps of the doctor blade were 50, 75, 100, and 150 μm, respectively, to finally prepare a mechanically gradient positive electrode (hereinafter referred to as the upper gradient positive electrode) with a thickness (excluding the aluminum foil thickness) of 70±7 μm. Using copper foil as a substrate, graphene slurry was coated and dried four times in order of increasing PVDF content (50℃). The coating gaps of the doctor blade were 75, 100, 150, and 200 μm, respectively, to finally prepare a mechanically gradient negative electrode (hereinafter referred to as the upper gradient negative electrode) with a thickness (excluding the copper foil thickness) of 105±10 μm.

[0037] In contrast, an electrode with decreasing PVDF content perpendicular to the current collector direction (hereinafter referred to as a lower gradient electrode) was prepared according to the above scheme, exhibiting a binder ratio distribution opposite to that of the upper gradient positive electrode prepared above. Simultaneously, an electrode with uniform PVDF content (hereinafter referred to as a uniform electrode) was also prepared. The difference between the three electrodes lies in the different PVDF distribution patterns perpendicular to the current collector direction, but the overall PVDF content is the same for all three, with PVDF contents of 4.25% and 4.75% in the positive and negative electrodes, respectively.

[0038] Mechanical property testing of mechanical gradient electrodes:

[0039] like Figure 1 As shown, a is a schematic diagram of a sample with a visualized bending radius. To facilitate the measurement of the bending radius, the electrode is adhered to a double-sided adhesive tape with a thickness of 200±10μm per layer. Then, the electrode sample is convexly bent, as shown. Figure 1 As shown in Figures b, c, and d, this double-sided tape provides 100μm scale intervals for measuring the bending radius, thus allowing the bending radius to be evaluated based on the number of layers. Once a breakage is observed under an optical microscope, its bendability can be assessed using the minimum bending radius without breakage. Figure 2 Optical images of the bent upper gradient positive electrode (bending radius 400 μm) and upper gradient negative electrode (bending radius 600 μm) show that no cracks were generated at this bending radius, indicating that the mechanical gradient electrode prepared by the present invention has excellent bending resistance.

[0040] Electrochemical performance testing of a mechanical gradient electrode based on a coin cell:

[0041] Electrochemical performance tests were performed on the top-gradient electrodes prepared in the examples. A 12.7 mm φ disc punch (TedPELLA, INC) was used to punch holes in the electrodes, and they were weighed using a microbalance (MSA6.6S-000-DM, Sartorius) with an accuracy of 0.001 mg. The electrodes were then assembled in an argon-filled glove box (MBRAUN). For the half-cell, lithium metal (Li) was used as both the counter and reference electrodes, and the electrolyte was ethylene carbonate (EC) / dimethyl carbonate (DMC) containing 1.0 M LiPF6 (volume ratio 1:1). CV, rate, and cycle tests were performed on an Arbin BT2000 battery tester. The voltage windows for the positive-Li, negative-Li, and positive-negative electrodes were 3.0 V to 4.3 V, 0.01 V to 3.0 V, and 0.1 V to 4.2 V, respectively. The test results are as follows: Figure 3 As shown, a) is the cyclic voltammogram (CV) of the upgradient electrode prepared in this invention, tested in half-cells and full-cells, respectively. b) and c) are the charge-discharge curves of the upgradient positive electrode / Li and upgradient negative electrode / Li half-cells, respectively. These data demonstrate that the mechanically gradient electrode prepared in this invention possesses excellent electrochemical performance.

[0042] To test the stability of the mechanical gradient electrode prepared in this invention, the three electrodes prepared in the examples were repeatedly folded and assembled into a coin cell for cycle stability testing. The test results are as follows: Figure 4As shown, a and b represent the cycle stability of the positive electrode before and after folding, respectively. c and d represent the cycle stability of the negative electrode before and after folding, respectively. For the folded electrode, the three types of electrodes have similar discharge capacity and cycle stability. However, for the folded electrode, the capacity of the upper gradient electrode is higher than that of the uniform electrode (the positive electrode is 124 mAh g / g). -1 The negative electrode is 303mAhg -1 ) and the lower gradient electrode (positive electrode is 119mAhg) -1 The negative electrode is 291mAhg -1 The high value indicates that the upper gradient electrode is less damaged during folding and has a higher cycle capacity retention rate.

[0043] Electrochemical performance testing of mechanical gradient electrodes based on pouch cells:

[0044] Pouch cells were prepared in a dry chamber with a dew point below -60°C. A 4mm wide aluminum sheet (EQ-PLiB-ATC4, MTI) was welded to an 18cm x 1.5cm positive electrode using an ultrasonic welder (MTI Corporation), and a 4mm wide nickel sheet (EQ-PLiB-ATC4, MTI) was welded to an 18cm x 1.6cm negative electrode. The electrodes were then secured to the separators with Kapton tape. The cells were encased in an aluminum-plastic film, and the three edges of the film were heat-sealed at 170°C using a heat sealer (TP701-BHEATSEAL, TESTERSANGYOCo., LTD.). After injecting 1mL of electrolyte, the pouch cells were sealed at 170°C using a vacuum sealer (TOKICO, Japan).

[0045] Figure 5 The figures show the electrochemical cycling test results and stable power supply under various conditions of the three electrodes prepared in the examples after being assembled into a pouch cell. a and b show the electrochemical cycling test results of the pouch cell (≈60mAh) under repeated bending, with the current density set to 0.06 mA / cm². -2 Where 'a' represents the areal capacity during the first 50 cycles, which assesses the battery's bend resistance by measuring the areal capacity during cyclic bending; and 'b' represents the areal capacity retention after 520 cycles, where the current density is reduced to 0.06 mA / cm² after the 500th cycle. -2During 50-520 cycles, the upper gradient electrode exhibited excellent stability (retaining 92.3% at 520 cycles), while the pouch cells prepared using uniform and lower gradient electrodes showed significant capacity decay (retaining 79.7% and 57.2% respectively at 520 cycles). Figure c illustrates the stable power supply provided to parallel LEDs by the mechanically gradient electrode prepared according to the present invention after being assembled into a pouch cell and subjected to various deformation modes (including twisting, folding, and knotting). The stable LED illumination indicates that the pouch cell has stable output.

[0046] The pouch cell fabricated using the top-gradient electrode was folded and subjected to charge-discharge tests. First, the pouch cell was cycled through 20 charge-discharge cycles to ensure stable charge-discharge performance. Then, the pouch cell was folded (fold radius 600 μm), and the areal current density was set to 0.06 mA / cm². 2 , Figure 6 To collect charge / discharge data during the 21st cycle, the surface energy density was 7.28 mWh / cm². 2 The FOM value is 121.3 mWh / cm³. 2 This indicates that folding does not immediately cause the electrode to decay, meaning that the mechanical gradient electrode prepared in this invention has excellent foldability.

[0047] Working Principle: For ordinary electrodes, their flexibility usually depends on the binder content. The higher the binder content, the better the electrode's flexibility. However, simply increasing the binder content can lead to a decrease in the battery's energy density. Since the electrode experiences different forces at different thicknesses during bending, the binder content at different thicknesses can be adjusted to meet requirements such as bending resistance. This method improves electrode flexibility while using less binder, ensuring high energy density. This invention is based on a traditional lithium-ion battery electrode preparation method. By controlling the PVDF content in the active material and graphene mixture, an electrode with a gradient change in PVDF content is prepared. This electrode, prepared based on a mechanical gradient, exhibits high energy density and excellent foldability.

[0048] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A method for fabricating a mechanically graded electrode for use in flexible batteries, characterized in that: Includes the following steps: S1. The active material, graphene and carbon black conductive agent are thoroughly mixed to obtain two mixtures, and each mixture is divided into four equal parts; S2. Dissolve PVDF powder in NMP solution to prepare PVDF solution; S3. Add the PVDF solution prepared in S2 to the four active material mixtures prepared in S1 to obtain four active material slurries with different PVDF contents; Add the PVDF solution prepared in S2 to the four graphene mixtures prepared in S1 to obtain four graphene slurries with different PVDF contents. Each portion of slurry is thoroughly mixed using a stirring degassing machine, and then NMP is added to each portion of slurry to ensure that the viscosity of each portion of slurry is consistent. S4. Use a scraper to scrape the active material slurry with the lowest PVDF content onto the current collector. After the coating is completed, place it in an oven to dry, and obtain a single-layer electrode. The graphene slurry with the lowest PVDF content was scraped onto the current collector using a scraper. After the coating was completed, it was placed in an oven to dry, thus obtaining a single-layer electrode. S5. Use different scrapers with larger coating gaps to repeat the operation in S4 with the remaining three portions of active material slurry in order of PVDF content from small to large, and finally obtain mechanical gradient electrode one; By successively using a scraper with a larger coating gap, the remaining three portions of graphene slurry are processed in order of increasing PVDF content, repeating the operation in step S4 to finally obtain the mechanical gradient electrode two.

2. The method for preparing a mechanical gradient electrode for flexible batteries according to claim 1, characterized in that: The active material is used to prepare the positive electrode, and graphene is used to prepare the negative electrode.

3. The method for preparing a mechanical gradient electrode for flexible batteries according to claim 1, characterized in that: The mass ratio of active material to carbon black conductive agent in S1 is 96:4, and the mass ratio of graphene to carbon black conductive agent is 96:

4.

4. The method for preparing a mechanical gradient electrode for flexible batteries according to claim 1, characterized in that: The active material in S1 is NCM111.

5. The method for preparing a mechanical gradient electrode for flexible batteries according to claim 1, characterized in that: The mass concentration of PVDF in S2 is 5%.

6. The method for preparing a mechanical gradient electrode for use in flexible batteries according to claim 1, characterized in that: The PVDF content in the active material slurry in S3 is 2%, 3.5%, 5%, and 6.5%, respectively; the PVDF content in the graphene slurry is 2.5%, 4.5%, 5%, and 7%.

7. The method for preparing a mechanical gradient electrode for use in flexible batteries according to claim 1, characterized in that: The current collector for coating the active material slurry in S4 is aluminum foil, and the current collector for coating the graphene slurry is copper foil.

8. The method for preparing a mechanical gradient electrode for flexible batteries according to claim 1, characterized in that: In S4, the coating gap of the doctor blade used for applying the active material slurry is 50 μm, and the coating gap of the doctor blade used for applying the graphene slurry is 75 μm.

9. The method for preparing a mechanical gradient electrode for use in flexible batteries according to claim 1, characterized in that: In S5, the coating gaps of the scraper used for applying the active material slurry are 75, 100, and 150 μm, respectively, and the coating gaps of the scraper used for applying the graphene slurry are 100, 150, and 200 μm, respectively.

Citation Information

Patent Citations

  • Integrated flexible electrode

    CN104916809A

  • Graphene electrode and preparation method therefor

    CN107546376A